Electrocardiographic Findings of Leprosy - Yildirim, Ersin; Secen, Ozlem; Demir, Betul; Bilen, Mehmet Nail (Aves, 2018)
Objective: The purpose of the present study was to investigate the effect of leprosy on basic electrocardiography (ECG) parameters. Materials and Methods: A total of 66 patients including 33 patients with leprosy (mean age: 70.06 years, 24 males) and 33 control patients (mean age: 56.66 years, 15 males) were included in the study. ECG recordings of all patients were obtained, and groups were compared in terms of heart rate, PR, QT, QTc, JTc, and T peak to T end (Tp-e) durations and branch blocks. Results: QT (391.30 vs. 367.66, p< 0.01), QTc (423.57 vs. 407.15, p< 0.01), and Tp-e (74.18 vs. 66.93, p< 0.001) intervals were significantly prolonged in the leprosy group. The left anterior hemiblock (LAH) was observed more in patients with leprosy (42.4% in 14 patients) than in the non-leprosy group (42.4% vs. 12.1%, p< 0.01). In addition, the rate of the unifascicularblock was significantly higher in the leprosy group (39.4% vs. 9.1%, p< 0.01). Conclusion: Leprosy has a significant effect on QT, QTc, and Tp-e intervals. Prolongation of the QT, QTc, and Tp-e intervals is an indicator of leprosy's effect on the cardiac autonomic system. The ratio of the LAH is also rather high, and that may be a marker of the area where leprosy is most effective on the heart.
Keywords: Leprosy; electrocardiogram; QT prolongation